PEMBINAAN MENTAL MELALUI PENDIDIKAN MASJID PADA REMAJA MASJID JAMI’ AL MUHARROMAH ULUJAMI PESANGGRAHAN JAKARTA SELATAN - Eddy Saputra; Achmad Muhajir (Fakultas Agama Islam Universitas Islam Jakarta, 2022)
Youth are a very productive age. The change from children to youth is a natural change that is accompanied by changes in attitudes and mindsets. Youth in general are an age group that requires extra attention because there is an attitude that always presents their existence or wants to be recognized. This attitude makes youth vulnerable to falling into negative things. Therefore, the great potential of adolescents must be directed at positive activities in order to explore their potential. The activities in the mosque, mental development in the activities are of course also accompanied by the tastes of the youth themselves. In the Jami' Al Muharromah mosque, Ulujami Village, South Jakarta, teenagers are active in several mosque youths using a mosque-based education approach. This study uses a qualitative method. The goal is that teenagers can increase their knowledge that mosques are not only used as places of worship. Mosques can also be used as non-formal educational institutions in order to foster the mentality of youth to be more focused so as to produce positive activities.